Chromatic aberrations correction of attosecond high-order harmonic beams by flat-top spatial shaping of the fundamental beam. (1st February 2023) - Veyrinas, K; Plach, M; Peschel, J; Hoflund, M; Catoire, F; Valentin, C; Smorenburg, P; Dacasa, H; Maclot, S; Guo, C; Wikmark, H; Zaïr, A; et al.
Abstract: Attosecond pulses created by high-order harmonic generation in gases often exhibit strong chromatic aberrations, arising from the broad bandwidth and wavelength-dependent nonlinear light–matter interaction. When the driving laser intensity varies spatially, as for Gaussian driving beams, the apparent source position of the harmonics differs significantly from one order to the next, thus affecting the achievable intensity and duration of the attosecond pulses when they are focused on a target. We show that these chromatic aberrations can be reduced by spatially shaping the fundamental beam to generate high-order harmonics with a driver having a flat-top profile inside the gas medium. By measuring both the intensity profile and wavefront for each harmonic in a plane, we access the extreme ultra-violet (XUV) beam properties and investigate these properties near focus. We observe that controlling chromatic aberrations by flat-top spatial shaping strongly reduces the variation of the XUV spectrum on the beam axis during propagation and, in return, the longitudinal sensitivity of both the temporal profiles and the temporal shifts of the focused attosecond pulses.